Kedudukan Transgender Dalam Sistem Kewarisan Islam dan Adat - Ash Shabah, Musyaffa Amin (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2021)
This study analyzes the position of transgender people in the distribution of inheritance from theperspective of Islamic law and customary law. This research is library research using the juridicalnormativeapproach and descriptive analysis data. The results of the study explain that there arethree elements of Islamic inheritance law, namely the heir, the heir, and the inheritance. The portionof the heirs has been determined in the Koran. The gender of the heir determines the amount of theshare of the inheritance to be received. In Islamic law, the position of inheritance for people who aretransgender is seen from their first gender at birth, and not determined after being transgender. Thisis because Islam forbids sex reassignment surgery because it has changed God’s creation. whereas inBalinese Customary Law, transgender actors are never recognized for their new status, before theyperform a religious ceremony. If this religious customary ceremony has been carried out and approvedby the traditional village leaders, then the applicant’s status is legal and customary.